PENGARUH KESESUAIAN HARGA DAN ULASAN ONLINE TERHADAP KEPUTUSAN PEMBELIAN WISATAWAN DI HOTEL ADIWANA MONKEY FOREST - Suardika, I Made; Sumerta, I Komang (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2023)
The study's objectives were to ascertain if price conformity and internet reviews had a concurrent, partial, and substantial impact on visitors' purchase choices at the Adiwana Monkey Forest Hotel. Up to 55 individuals were used in the purposive random sampling approach to estimate the sample size. Travellers from Australia, Europe, and Asia who stayed at the Adiwana Monkey Forest Hotel comprised the criteria that the writers employed in this research. The traditional assumption test, analysis of multiple linear regression coefficients, determination analysis, partial significance test (t-test), and bersama-samaeous significance test analysis (F-test) were all used to analyse the data. The findings demonstrated a favourable and considerable effect on price suitability and internet reviews concurrently or in part on visitors' purchase choices at the Adiwana Monkey Forest hotel.